Academic Dishonesty and Whistleblowing Intentions Among Economics Students - Arifah, Siti; Pramudyastuti, Octavia Lhaksmi; Mulyadi (Yayasan Sinergi Kawula Muda, 2025)
This study examines economics students' perceptions of academic dishonesty and their willingness to engage in whistleblowing within higher education institutions. Academic dishonesty remains a persistent issue in universities, potentially undermining students' ethical development and professional integrity. While prior research has extensively explored the prevalence and causes of academic dishonesty, limited attention has been given to students' reluctance to report such misconduct. This study employs a descriptive quantitative approach and collects data from 160 economics students in Central Java and the Special Region of Yogyakarta (DIY) using purposive sampling. The findings indicate that the majority of students have engaged in various forms of academic dishonesty, including cheating, plagiarism, using unauthorized resources, and paying others to complete assignments. Despite recognizing the ethical implications, students demonstrate low willingness to report dishonest behavior. Key barriers include institutional shortcomings, such as the absence of a clear whistleblowing mechanism, lack of protection for whistleblowers, and fear of retaliation or social ostracism. The study emphasizes the need for a structured and confidential whistleblowing system to foster academic integrity. Universities should implement secure reporting channels, strengthen ethical education, and cultivate an institutional culture that supports honesty and accountability. By addressing these challenges, higher education institutions can enhance students' ethical awareness and commitment to academic integrity, ultimately improving the quality of education.